Incremental prognostic value of positron emission tomography-derived myocardial flow reserve in patients with and without diabetes mellitus. (23rd February 2023) - Aljizeeri, Ahmed; Ahmed, Ahmed Ibrahim; Suliman, Ihab; Alfaris, Mousa Alali; Elneama, Awadelkarim; Al-Mallah, Mouaz H
Abstract: Aims: We aimed to assess the incremental prognostic value of positron emission tomography (PET)-derived myocardial flow reserve (MFR) among patients with diabetes and those without diabetes. Methods and results: Consecutive patients with clinically indicated PET MPI for suspected or established coronary artery disease (CAD) were included. Myocardial blood flow (MBF) in mL/min/g was obtained from dynamic images at rest and stress, while MFR was calculated as the ratio of stress to rest MBF. Patients were followed from the date of PET imaging for the occurrence of the primary outcome (composite of all-cause death, myocardial infarction, and un-planned percutaneous coronary intervention/coronary artery bypass graft occurring more than 90 days after imaging). The final cohort consisted of 6019 patients (63% with diabetes) (mean age 61 ± 11 years, 45% female, 55% obese, 76% hypertensive, and 62% dyslipidaemia). Over half (53%) of the patients had an impaired MFR (<2). During a median follow-up of 22.6 (7.8–42.5) months, 619 patients (10%, 3.8 per 1000 person-years) experienced the primary outcome. Impaired MFR (MFR < 2) was significantly associated with the primary outcome in patients with and without diabetes (diabetes: HR 1.8, 95% CI 1.4–2.3, P < 0.001; no diabetes: 1.4, 95% CI 1.0–2.1, P = 0.046). There was no interaction between diabetes status and MFR ( P = 0.234). Results were consistent across subgroups of patients with no CAD and normal perfusion study. Conclusion: PET-derived MFR has a strong independent and incremental prognostic role in patients with diabetes and those without diabetes. Graphical Abstract: Graphical Abstract